Hybrid hydrogen energy stored in stand-alone power system - Goh, Wei Chiun (Curtin University, 2008)
A stand-alone power system is an autonomous system that supplies electricity to the user load without being connected to the electric grid. This kind of decentralized system is frequently located in remote and inaccessible areas. The purpose of this thesis is the modelling and simulation of a solar hydrogen hybrid power system to supply the typical residential electric customers in stand alone. It couples a photovoltaic (PV) generator, an alkaline water electrolyzer, a storage gas tank, a proton exchange membrane fuel cell (PEMFC), and power conditioning units (PCU) to give different system topologies. The overall mathematical model was obtained by integrating between their various subsystems models derived from literature. The system is intended to be an environmentally friendly solution since it tries maximizing the use of a renewable energy source. The results of the simulations showed that the hydrogen is one of the future energy storage mediums by using both TRNSYS software and HOMER software.